Decreasing influence of arbitrarily applicable verbal relations of recreational gamblers: A randomized controlled trial. Issue 1 (5th October 2018) - Belisle, Jordan; Paliliunas, Dana; Dixon, Mark R.; Speelman, Ryan C.
Abstract : Twenty‐one recreational gamblers were randomly assigned to two groups; one group was exposed to a conditional discrimination relational training task to bias choice allocation to a black machine presented concurrently with a red machine, and the other group underwent the same relational training task immediately followed by a defusion procedure, designed to expand upon the relations developed in the initial relational task. Both groups completed a simulated slot‐machine task before and after the relational training task, with or without the defusion procedure. Results showed that 9 of 11 participants in the relational training only group showed an increased bias toward the black machine, compared to only 4 of 10 in the relational training plus defusion group; this latter group also showed greater matched responding. Results suggest that expanding verbal–relational networks may reduce the influence of any single verbal relation on gambling choice behavior.